2018
DOI: 10.1177/0890117118761887
|View full text |Cite
|
Sign up to set email alerts
|

Supporting a Culture of Health in the Workplace: A Review of Evidence-Based Elements

Abstract: A considerable number of cross-sectional studies demonstrated significant and salient correlations between culture of health elements and the health and safety of employees, but more research is needed to examine causality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
43
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 81 publications
(44 citation statements)
references
References 105 publications
(189 reference statements)
0
43
0
Order By: Relevance
“…These are among the recommended practices represented in the broader body of "culture of health" research that reinforces the importance of using socio-ecological approaches to create environments and systems within organizations that support HWB programs aimed at individual behavior change. 36 While the importance of organizational and leadership support for the effectiveness of HWB initiatives has long been recognized, 17,21,25,28,33,34,37 research linking specific practices with different types of outcomes is just beginning to emerge. 18 Leadership support is particularly evident in previous research on practices associated with effective HWB initiatives.…”
Section: Discussionmentioning
confidence: 99%
“…These are among the recommended practices represented in the broader body of "culture of health" research that reinforces the importance of using socio-ecological approaches to create environments and systems within organizations that support HWB programs aimed at individual behavior change. 36 While the importance of organizational and leadership support for the effectiveness of HWB initiatives has long been recognized, 17,21,25,28,33,34,37 research linking specific practices with different types of outcomes is just beginning to emerge. 18 Leadership support is particularly evident in previous research on practices associated with effective HWB initiatives.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have found that adopting environmental interventions alone is completely ineffective in improving employees' health behaviors and health status (42)(43)(44)(45). However, combined with other behavioral interventions, environmental intervention can help to promote the effectiveness of WHP (46,47). Therefore, most countries now encourage comprehensive WHP as much as possible.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, high-stress employees who are satisfied with their jobs also had a higher risk of long-term sickness absence; therefore, the encouragement of physician interview for them should not be ignored. It should also be noted that corporate culture and policy play an important role in job stress and health outcomes among employees 34,35) . For example, our surveyed company is listed on the major stock exchange and provides employees with 30 days of paid leave and a standard benefits package, including leave compensation and employment insurance, which may influence long-term sickness absence.…”
Section: Discussionmentioning
confidence: 99%